Local Wisdom-Based Science and Environmental Education Management: Perspectives from the Bunggu Indigenous Community - Albar; Daswati; Muhammad Nawawi; Syufri (Postgraduate, University of Mataram, 2025)
Strengthening science and environmental education through local wisdom is a strategic approach to creating contextual, relevant, and sustainable learning, particularly within indigenous communities. This study aims to explore how the Bunggu Indigenous Community in Pasangkayu, Indonesia, integrates local wisdom values into the management of science and environmental education. Utilizing a qualitative case study approach, data were collected through in-depth interviews, participatory observations, and document analysis involving traditional leaders, educators, and educational stakeholders. The findings reveal that scientific concepts such as ecology, environmental conservation, natural resource management, and traditional technology are taught through culturally inherited practices. The community's education management combines local wisdom with formal curricula, resulting in adaptive and contextual strategies for science and environmental learning. These findings emphasize that integrating local wisdom into science and environmental education not only enriches the learning process but also strengthens ecological awareness, cultural identity, and community participation in environmental preservation. This study contributes to the development of an education management model that is more responsive to local cultural contexts and highlights the need for educational policies that support local wisdom-based learning.